2022
DOI: 10.3390/ijerph19127515
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Toxoplasma gondii IgG and Liver Injury in US Adults

Abstract: Background: Toxoplasma gondii (T. gondii) is a ubiquitous obligatory intracellular parasite which infects over 40 million Americans and causes toxoplasmosis. Inside the human body, T. gondii can damage tissues and invade vital organs. Methods: This study evaluated the association of T. gondii infection and liver disease using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2010, with a sample size of 3371 participants (age 20–80 years). Toxoplasma infection was determined by the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This study hypothesized that exposure to Toxoplasma gondii infection has a negative effect on the cardiovascular system, renal system, and hepatic system simultaneously by causing inflammation, oxidative stress, and tissue damage, leading to an increased risk of cardiovascular disease, chronic kidney disease, and chronic liver disease. To test this hypothesis, we examined the effect of T. gondii on an overall cardiovascular biomarker index (OCBI) developed in our prior work [ 5 ], a chronic liver disease index, and a chronic kidney disease index used in our prior work [ 11 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study hypothesized that exposure to Toxoplasma gondii infection has a negative effect on the cardiovascular system, renal system, and hepatic system simultaneously by causing inflammation, oxidative stress, and tissue damage, leading to an increased risk of cardiovascular disease, chronic kidney disease, and chronic liver disease. To test this hypothesis, we examined the effect of T. gondii on an overall cardiovascular biomarker index (OCBI) developed in our prior work [ 5 ], a chronic liver disease index, and a chronic kidney disease index used in our prior work [ 11 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, cardiovascular, kidney, and liver health were evaluated using biomarker indexes developed in our previous studies [ 5 , 11 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Borges and co-authors [11] compared the detection of immunoglobulin isotypes and subclasses against Toxoplasma gondii soluble antigen in serum and colostrum samples from puerperal women, and reported that serum and colostrum immunoglobulins of different classes and subclasses provide a wealth of information about exposure to toxoplasmosis. A recent case-control study by Babekir and colleagues [12] evaluated the association of T. gondii infection and liver disease, and found serum T. gondii IgG+ antibody to be significantly associated with liver injury biomarkers and an increased risk of chronic liver disease and nonalcoholic fatty liver disease, demonstrating the value of serological tests in toxoplasmosis.…”
Section: Case Reportmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD), whose pathogenesis is linked with liver injury commonly measured by alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyltransferase (GGT), is the most common chronic liver disease worldwide. 1 3 Globally, the estimated prevalence of NAFLD in the general adult population is 32.4% and has increased from 25.5% in 2005 to 37.8% in 2016. 4 In China, the prevalence of NAFLD is nearly 30% and has increased by 10% from 2008 to 2018.…”
Section: Introductionmentioning
confidence: 99%